Disentangling, again, the drivers of population decline for two harvested species: a response to Prasad et al. (2014). Issue 3 (15th April 2014) - Ticktin, Tamara; Ganesan, Rengaian; Paramesha, Mallegowda; Setty, Siddappa; Hulme, Philip
Summary Ticktin et al. (2012) (Journal of Applied Ecology, 49, 774) assessed the dynamics of two Indian tree species (Phyllanthus emblica and P. indofischeri) and showed that although fruit harvest can decrease long‐term population growth rates (λ), the principal drivers of decline are mistletoe infestation and invasion of an exotic shrub. Prasad et al. (2014) (Journal of Applied Ecology, 51, doi: 10.1111/1365‐2664.12170) questioned Ticktin et al.'s approach, showed that P. emblica λ values increased when fruit harvest was banned and concluded that fruit harvest has a significant negative effect. We demonstrate that Prasad et al.'s analysis is fundamentally flawed and that our conclusions hold firm. We clarify that our models are built from empirical data collected from field plots. We use life table response experiments to demonstrate that the increase in P. emblica λs after the fruit harvest ban is due to higher adult survival and unrelated to fruit harvest. P. indofischeri populations show no such increase. We demonstrate that our results and the literature strongly back up our management recommendations to control mistletoe and the invasive shrub, and protect amla saplings. Synthesis and applications. Prasad et al. (2014) confound the effects of time and treatment and therefore reach erroneous conclusions. This highlights the importance of careful analyses to disentangle the effects of multiple drivers of decline for species at risk.